SISTEM INFORMASI PEMESANAN ONLINE PADA PERCETAKAN CV. AMALIA PERCETAKAN PALEMBANG BERBASIS WEB - Sayuti, Akhmad; Davizan, Serry; Agustian, Ade; Irwansyah, Irwansyah; Harist, Abdul (Program Vokasi Universitas Negeri Gorontalo, 2024)
Amalia Printing Palembang is a company operating in the printing services sector. In facing competition and meeting increasingly dynamic customer needs, a web-based information system is needed that can simplify the process of ordering products online. This research aims to design and develop an Online Ordering Information System that can provide printing product ordering services more efficiently and structured. This system allows customers to view product catalogs, place orders, upload design files, and monitor order status in real-time. Apart from that, the system is also equipped with customer registration features, online payment methods, and notifications regarding order status. On the administrator side, there is a dashboard that supports order management, payment confirmation, and transaction reporting in an integrated manner. System development uses web technology with the Laravel framework for the backend, MySQL as the database, and an interactive interface designed using HTML, CSS, and JavaScript. This system is expected to increase CV operational efficiency. Amalia Printing and provide a better customer experience. By implementing this system, companies can provide more modern, fast and satisfying services according to the needs of today's digital market.